PHILOSOPHY OF DIALOGUE IN THE INFORMATION AGE CULTURE - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In the article the philosophical study of the phenomenon of dialogue is carried out and its specific characteristics in the culture of the information age are revealed.